2017
DOI: 10.1519/ssc.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Force-Velocity Profile of Athletes Using Weightlifting Derivatives

Abstract: WEIGHTLIFTING MOVEMENTS AND THEIR DERIVATIVES MAY BE IMPLEMENTED IN A SEQUENCED PROGRESSION THROUGHOUT THE TRAINING YEAR TO OPTIMIZE THE DEVELOPMENT OF AN ATHLETE'S STRENGTH, RATE OF FORCE DEVELOPMENT, AND POWER OUTPUT. WEIGHTLIFTING MOVEMENTS AND THEIR DERIVATIVES CAN BE PROGRAMMED EFFECTIVELY BY CONSIDERING THEIR FORCE–VELOCITY CHARACTERISTICS AND PHYSIOLOGICAL UNDERPINNINGS TO MEET THE SPECIFIC TRAINING GOALS OF RESISTANCE TRAINING PHASES IN ACCORDANCE WITH THE TYPICAL APPLICATION OF PERIODIZED TRAINING PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
127
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 78 publications
(59 reference statements)
0
127
0
2
Order By: Relevance
“…Thus, the loads implemented for these exercises may not have provided an adequate load or volume stimulus to the Pull group, which may have prevented them from displaying greater training benefits compared to the Catch group. Given that weightlifting pulling derivatives may produce greater force and velocity characteristics, dependent on the load used (43), researchers may consider investigating the training effects of weightlifting pulling derivatives that use loads which emphasize either a force or velocity overload stimulus, as described by Suchomel et al, (43), compared to training with weightlifting catching derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the loads implemented for these exercises may not have provided an adequate load or volume stimulus to the Pull group, which may have prevented them from displaying greater training benefits compared to the Catch group. Given that weightlifting pulling derivatives may produce greater force and velocity characteristics, dependent on the load used (43), researchers may consider investigating the training effects of weightlifting pulling derivatives that use loads which emphasize either a force or velocity overload stimulus, as described by Suchomel et al, (43), compared to training with weightlifting catching derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of weightlifting derivatives also suggested that variations of the PC, which omit the catch phase, namely the clean pull, mid-thigh pull, jump shrug and hang high pull, may be advantageous when training athletes who are less proficient with full weightlifting movements that include the catch phase (41,43). This is supported by additional research that has suggested the use of associate exercises that enhance explosive strength during the second pull movement in less skillful athletes (25).…”
Section: Introductionmentioning
confidence: 95%
“…Jump squats 4. Weightlifting derivatives including: jump shrugs and hang clean pulls Based on training recommendations [ 81 , 83 , 98 , 101 , 108 , 148 ] Sasaki et al [ 42 ] Male soccer 180° turn—PP 0.44 ± 0.07 Spiteri et al [ 106 ] Female basketball 180° turn—PP 0.42 ± 0.03 to 0.47 ± 0.04 Jones et al [ 36 ] Female soccer 180° turn—PP (4.03 ± 0.2 m·s −1 ) 0.517 ± 0.082 Dos’Santos et al [ 59 ] Male team sport 180° turn—PP 0.46 ± 0.10 Note: Strength training should not be omitted and overlooked, as an underpinning foundation of strength is required for effective use of plyometrics, ballistic training, and weightlifting exercises [ 81 , 83 , 98 , 101 , 108 , 148 ]. Shorter GCTs, and greater braking and propulsive forces have been identified as determinants of faster COD speed performance [ 40 , 42 , 59 , 83 , 106 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,11 However, based on our findings (Figure 3), the lifters' receiving positions might not have been strictly controlled, which could be the primary factor for such inconsistency. It has been stated in a journal article, 19 a review article, 1 and original research articles 6-10 that the optimal load for Olympic weight-lifting exercises that include the motion of receiving the bar after the second pull phase is a submaximal load. However, because it is possible that the success criterion (quarter squat vs parallel squat) is a determinant of the optimal load for HPC, the results of the previous studies and their interpretations should be applied with caution in strength and conditioning settings.…”
Section: Discussionmentioning
confidence: 99%